2014
DOI: 10.4049/jimmunol.1303150
|View full text |Cite
|
Sign up to set email alerts
|

Pig Skin Includes Dendritic Cell Subsets Transcriptomically Related to Human CD1a and CD14 Dendritic Cells Presenting Different Migrating Behaviors and T Cell Activation Capacities

Abstract: Swine skin is one of the best structural models for human skin, widely used to probe drug transcutaneous passage and to test new skin vaccination devices. However, little is known about its composition in immune cells, and among them dendritic cells (DC), that are essential in the initiation of the immune response. After a first seminal work describing four different DC subpopulations in pig skin, we hereafter deepen the characterization of these cells, showing the similarities between swine DC subsets and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
62
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 89 publications
2
62
0
Order By: Relevance
“…Transcriptomic and functional studies demonstrated that the CD163 low population expressed high levels of CD172a, were XCR1 negative, and shared gene expression with cDC2 suggesting they are the tissue resident equivalents of the CD1 + subpopulation described here. Likewise, the CD172a − cells were the only population to express XCR1, therefore likely to resemble the cDC1 population described in human and mouse and the CD1 − population described here3637.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Transcriptomic and functional studies demonstrated that the CD163 low population expressed high levels of CD172a, were XCR1 negative, and shared gene expression with cDC2 suggesting they are the tissue resident equivalents of the CD1 + subpopulation described here. Likewise, the CD172a − cells were the only population to express XCR1, therefore likely to resemble the cDC1 population described in human and mouse and the CD1 − population described here3637.…”
Section: Discussionmentioning
confidence: 66%
“…With the intention of identifying cDC in the skin as targets for vaccination strategies others have demonstrated that porcine skin CD163 low cells share phenotypic and transcriptomic features consistent with the cDC2, and a CD172a − subset orthologous to cDC1 cells3536. Similar populations have also recently been identified in the porcine lung37.…”
mentioning
confidence: 99%
“…Even under conditions where the experimental design is favorable to the use of hierarchical clustering, GSEA ensures of the robustness of interpretation. GSEA has been used by us and others to perform cross-species comparisons (5, 19, 29, 42, 7678). GSEA notably displays advantages and drawbacks distinct from those of hierarchical clustering.…”
Section: Discussionmentioning
confidence: 99%
“…The cRNAs (600 ng) were fragmented and used for hybridization on custom-designed Agilent ovine and porcine arrays. Our arrays for sheep and pig were custom-designed based on the commercial ovine Agilent arrays for these two species, as previously described (28, 29). In brief, the commercial probes with poor Sigreannot scores (30) were replaced with new probes designed using the e-array software from Agilent Technologies and including ovine or porcine orthologs of genes known to be selectively expressed in human and mouse DC subsets (15).…”
Section: Methodsmentioning
confidence: 99%
“…Swine are an important animal model for human research due to their physiologic, anatomic and immunologic similarity. In the field of DCs, Marquet et al (2011Marquet et al ( , 2014 characterized the skin cDCs and found that the CD172a − XCR1 + (which is homologous to human BDCA3 + ) and CD172a + XCR1 − (homologous to human BDCA1 + ) subsets correspond to cDC1 and cDC2, respectively (Marquet et al, 2011;Marquet et al, 2014). Maisonnasse et al (2016a,b) described similar results in lung and bronchoalveolar lavage (Maisonnasse et al, 2016a;Maisonnasse et al, 2016b).…”
Section: Introductionmentioning
confidence: 91%